The Myth of Sayyidina Ali’s “Illegitimate Child” Crocodile: The Phenomenon of Syncretism Among Coastal Communities in West Kalimantan - Eka Hendry Ar.; Ria Hayatunnur Taqwa; Syf. Fatimah (Al-Albab, 2017)
West Kalimantan has various local cultural treasures in the form of ritual traditions, arts as well as oral traditions in the form of pantun, abstinence, legends, and myths. The cultural treasures spread throughout the West Kalimantan regions, one of which is found in the coastal area of the Province. The treasure that attracts the attention of the researchers is the oral tradition of the myth found in coastal areas of Kubu and Teluk Pakedai. The myth is the crocodile of anak kampang Sayyidina Ali (Sayyidina Ali‘s “illegitimate child“). This myth contains many dimensions, ranging from the dimensions of local culture and religious views to syncretism. The researchers also assume that the myth contains a negative stereotype against Shi’a. This research attempts to reconstruct the culture of the myth in various spectra. This research uses ethnography method. It reveals some interesting aspects such as euhemerism of the figure of Imam Ali. The myth also contains a very strong syncretic content, thus arising a paradox of the existing character, between glorifying and degrading. It arises because of a thorough understanding of the history of Islam on the one hand, and the strong style of local tradition held by the community on the other. However, the myth is quite functional for society, because it indirectly instills awareness about nature conservation. Finally, in relation to the allegations of political motives in myth, the researchers found no sufficient data, but the academic suspicion of the researchers had a strong belief in it.